Mass Spectrometry Supports That the Structure of Circulating Human Insulin-Like Factor 3 Is a Heterodimer - Albrethsen, Jakob; Juul, Anders; Andersson, Anna-Maria (Frontiers in Endocrinology, 2020)
The structure of the testicular peptide hormone Insulin-like factor 3 (INSL3) has been the subject of discussion for more than decade. Some studies support that the central C-domain of INSL3 is proteolytically removed and that INSL3 is secreted by the testicular Leydig cells into circulation as a small heterodimer consisting of an A and B chain linked by two disulfide bridges. Other studies support that the INSL3 peptide remains uncleaved, and that the predominant structure of circulating INSL3 is the larger pro-form. Furthermore, the structure of INSL3 could differ between species and both structural forms of INSL3 could in principle be present in circulation. Recently, we have developed a mass spectrometry (MS)-based method for INSL3 in human serum that provides new information about the structure of circulating INSL3. Based on recent and newly presented data we argue that in healthy men the common, and probably only, form of circulating INSL3 is the smaller AB heterodimer. For the first time we demonstrate that the same analytical principle, with slight modifications, can also be applied to sera from other species and we show that the INSL3 AB heterodimer is also present in serum from rodents. Improved understanding of the structure and biochemistry of circulating INSL3 could be valuable for the interpretation of INSL3 as a marker for reproductive and developmental disorders in humans and domesticated animals.